Investigating the Relationship between Environmental Factors and the Incidence of Multiple Sclerosis in Three Regions of Iran: A Case-control Study - Rezaei, Sajjad; Moradi, Maryam; Gharedashi, Zahra; Khosravi, Fatemeh; Hosseini-Moghaddam, Fatemeh; Basiri Moghaddam, Mehrsa (Advances in Nursing & Midwifery, 2025)
Abstract Introduction: Multiple sclerosis is one of the most prevalent debilitating neurological diseases among young people. Multiple sclerosis is a multifactorial disease in which both environmental and genetic factors are involved. Despite numerous studies conducted in this field, it remains a challenging topic. Therefore the present study aimed to explore the environmental factors associated with multiple sclerosis. Methods: This case-control study was conducted in 2020-21 in three geographical areas of Iran. A total number of 445 subjects were included in the study, among whom 172 belonged to the case group and 273 to the control group. The inclusion criteria for patients were the confirmation of the disease by a neurologist, the age range from 15 to 50 years, full consciousness, not having acute or critical conditions of MS disease. The inclusion criteria for healthy subjects were not having the MS, not having any neuro-inflammatory peripheral disease, not having a cancer. The patient participants were randomly selected from the medical records of the MS Association of each city. The control group was randomly selected from among the people visiting the medical centers of each city. The collected data were punched into SPSS 20. Descriptive and inferential statistics including mean, standard deviation, frequency and chi-square were used to describe the research variables. Mann-Whitney U-test was used to compare the mean of interval variables in two groups, and chi-square test was used to determine the relationship between qualitative variables in two groups. A logistic regression analysis was used to estimate the relationship between risk factors and the disease. Results: There was a significant difference between the two groups in terms of the duration of sunbathing , OCP, gender , history of blood transfusion , family history of MS , history of crisis , physical activity before illness , history of accident , job, ethnicity, predominant type of cooking, consumption of liquids and tea, salt consumption, Infant nutrition, consumption of vegetables and chicken, consumption of canned food, dairy products, nuts and beans (p<0.05).Bivariate logistic regression analysis of factors associated with multiple sclerosis showed that the most influential factors in the disease were: positive family history, history of accidents and trauma, baby nursing, and a high-salt diet (p <0.05). Conclusions: The successful control of this disease depends on the identification of the complex network of factors. Despite the many researches about the factors related to MS, it seems that this issue has many complications and detailed and advanced studies should be done in this field. By better understanding these factors, we can create preventative strategies to reduce the risk of developing MS, develop more effective treatments, and lessen the burden of the disease on affected individuals and society